Republic of Tajikistan : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Tajikistan is not a HIPC country. It is, however, eligible under the MDRI because it had a per capita annual GDP of below USD 380 as of 2004. Staff is of the view that all criteria have been met, and recommends that the Board determine that Tajikistan qualifies for immediate debt relief under the MDRI.